Regional head elections, high-cost politics, and corruption in Indonesia - Leo Agustino; M Dian Hikmawan; Jonah Silas (Department of Government Studies Universitas Muhammadiyah Makassar, 2023)
Direct regional head elections or direct election give rise to two faces for Indonesian politics. On the one hand, a positive face towards democracy; on the other hand, it displays a negative impact. Its positive impacts include efforts to strengthen the political legitimacy of local governments; achieving political empowerment of citizens; institutionalizing checks and balances mechanisms between institutions in the region; and the emergence of female regional heads. Meanwhile, among the negative impacts of direct elections are the high costs of politics. The research presents a qualitative approach with data collection techniques in the form of literature studies, observations, and interviews. This paper marks aspects high costs were caused by several factors, such as candidacy buying, campaign costs, witness fees during the election, political consultant fees, and appeal fees to the Constitutional Court. Therefore, it is not surprising that the winning contestants will try to return to their capital by means of corruption. This research implies at least four modes of return of political capital exist for regional heads, namely: bribery in obtaining permits; buying and selling positions; bribes in the procurement of projects and goods; and manipulation of social assistance. Referring to this dilemma, it turns out that the election still leaves a huge amount of homework for deepening democracy in Indonesia.